Imaging PAM fluorometry reveals stable photosynthetic efficiency in multibiont symbioses on coral reefs - Bähr, Susanne; van der Meij, Sancia E. T.; Santoro, Erika P.; Benzoni, Francesca (Frontiers in Marine Science, 2025)
Many cryptic invertebrates residing within the coral reef matrix exhibit symbiotic relationships with scleractinian hosts. Despite their contribution to reef biodiversity, these host-symbiont associations and their potential impact on coral fitness and survival remain poorly understood. Additionally, the presence of symbiotic Symbiodiniaceae within coral tissue further enhances the complexity of these multibiont relationships. This study focuses on coral-dwelling gall crabs (Cryptochiridae) that structurally modify their host’s skeleton. By using Imaging Pulse-Amplitude-Modulated (PAM) fluorometry, which provides a spatial assessment of maximum quantum yields of PSII fluorescence (Fv/Fm values), we investigated the impact of cryptochirids on the photosynthetic performance of the corals’ symbiotic algae in eight coral-crab associations, encompassing six coral species from the central Red Sea. Visual output of Fv/Fm values at coral fragment scale showed no distinct effects of cryptochirid presence on Symbiodiniaceae in uninhabited areas. However, Fv/Fm measurements near the crabs’ dwellings (<3 mm) showed significant increases (3–6%) in three colonies and significant decreases (4–12%) in two colonies. Although the exact cause of the increased photosynthetic efficiency in two associations remains speculative, the presence of filamentous algae and trapped sediment near the dwelling likely accounts for the reduced values observed in one of the Echinopora associations. Considering that the photosynthetic efficiency of Symbiodiniaceae in most studied corals was not affected by the crabs, we suggest that their presence has no widespread negative impact on these multisymbiotic relationships. This study highlights the need for additional research to better understand the ecological function of multibiont assemblages on coral reefs.